Elastase inhibition by natural flavonoids: mechanistic insights and potential therapeutic applications - Lin, Lihao; Yao, Hongliu; Fu, Jinfeng; Zhang, Wenhui; Li, Yongxue; Wang, Yan; Shen, Haoyu; Mo, Jingang; Guan, Yi (Frontiers in Nutrition, 2025)
Overproduction of elastase plays an important role in the progression of inflammatory diseases. In this study, we compared the inhibitory effects of structurally similar bioactive flavonoids (quercetin, hyperoside, luteolin, and luteoloside) on elastase activity and elucidated their mechanisms of action. Enzyme inhibition assays and fluorescence, ultraviolet–visible (UV–vis), Fourier transform infrared (FT-IR), and circular dichroism (CD) spectroscopy examinations assessed the interactions among flavonoids, elastase, and elastase conformational changes. Molecular docking analyzed binding interactions. Thermodynamic parameters were calculated to determine the forces that stabilize the flavonoid-elastase complexes. Luteolin strongly inhibited elastase, followed by hyperoside, quercetin, and luteoloside. Fluorescence spectroscopy revealed static quenching of all flavonoids, with binding distances indicating non-radiative energy transfer between the flavonoids and elastase. Thermodynamic analysis revealed that hydrogen bonds and van der Waals forces primarily stabilized hyperoside and luteolin, whereas electrostatic interactions stabilized quercetin and luteoloside. UV–vis, FT-IR, and CD spectroscopy confirmed that flavonoids induced conformational changes in elastase, and increased random coil content was correlated with inhibitory strength. Molecular docking results supported these findings, with strong binding affinities between flavonoids and elastase, particularly luteolin and hyperosides. The four natural flavonoids inhibited elastase by altering their secondary structures. Modifications at positions 3 (C-ring) and 7 (A-ring) of flavonoids can enhance elastase inhibition. These findings provide a scientific basis for the development of flavonoid-based anti-inflammatory therapies targeting elastase-related diseases.